Esquistossomose mansoni no sudoeste do Estado de Minas Gerais (Brasil) Schistosomiasis mansoni in the Southwest of the State of Minas Gerais (Brazil) - Omar dos Santos Carvalho; Cristiano Lara Massara; Roberto Sena Rocha; Naftale Katz (Universidade de São Paulo, 1989)
É descrito um foco de esquistossomose mansoni, no Município de Passos, sudoeste do Estado de Minas Gerais, região até agora considerada livre da endemia. Relata-se a presença de Biomphalaria glabrata parasitada por Schistosoma mansoni, em um clube campestre, nas imediações da cidade, além de quatro crianças, residentes neste clube, com esquistossomose autóctone. Observa-se ainda, a existência de B. straminea, não infectada, nos tanques da Estação de Hidrobiologia e Piscicultura de Furnas. É discutida a importância epidemiológica da esquistossomose para a região. A new focus of schisiosomiasis mansoni at Passos, a town in the Southwest of the State of Minas Gerais (Brazil), region until now considered free of the disease is reported. Malacological surveys showed Biophalaria glabrata naturally infected with Schistosoma mansoni in a country club near Passos. All B. straminea captured at the pisciculture station of the Furnas hydroeletric dam were negative. Six out of seven individuals living in the country club were found to be infected with S. mansoni, including four children who had never been out of Passos. The epidemiological importance of these findings is discussed.